Information Broadcasting Concerning Publicity and Public Participation in Development Plan - et. al., Norizan Rameli, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Malaysian Law stipulates the public society should be involved in development planning to assure thorough and comprehensive planning is made to fulfill the needs and aspirations of the society coming from multiracial and ethnicities. However, their knowledge about public participation in development planning is still in question. The participation is in fact a great opportunity for the society to play a part in shaping and influencing the objective and direction of future developments. Public participation is required in every stages of development planning such as Local Plan to ensure effectiveness of the planning system. Therefore it is crucial for the information concerning the publicity and public participation to reach targetted group through accessible broadcasting method that matched with present-day. This paper reviews their knowledge towards public participation programs. This quantitative study also discovers respondents' views on the method of information broadcasting through social media. The result shows their knowledge about public participation in planning process is considerately very low. Additionally, the study discovers that social media is highly influential among respondents where it should be used to increase public participation in development planning.